Psychological interventions mitigated occupational stress in high-risk workers in Shenzhen, China - Naixing Zhang; Wei Zhou; Aipin Xiao; Shaofan Weng; Liuzhuo Zhang; Dexiang Zhu; Jinlin Wang; Ling Nian; Dafeng Lin; Dafeng Lin (Frontiers in Public Health)
IntroductionOccupational stress has emerged as a significant factor impacting the physical and mental wellbeing of workers in China. This study investigated occupational stress among the potential high-risk workers in Shenzhen, China, and evaluated the psychological interventions subsequently implemented.MethodsA stratified cluster sampling method was employed, randomly selecting one quarter of clusters (clustered by work unit) from each of the four strata (stratified by occupational category) including firefighters, bus drivers, video display terminal (VDT) operators, and port workers, respectively, as the study cohort. Occupational stress was assessed at baseline and after psychological interventions using the “Job Content Questionnaire.” The interventions primarily included regular occupational mental health training and group psychological support sessions. Baseline occupational stress detection rates and high social support rates were analyzed, along with their post-intervention changes, to comprehensively evaluate the intervention effectiveness.ResultsThe cohort comprised 3,237 participants, with a median age of 31 years, 92.18% were male, and 96.14% were Han Chinese. The baseline occupational stress detection rate was 52.73%, and the high social support rate was 21.19%. Comparative analysis revealed statistically significant differences (all P < 0.05) in occupational stress detection rates across different age groups, ethnicities, education levels, smoking habits, weekly working hours, and working years. Similarly, high social support rates varied significantly (all P < 0.05) by age, education level, marital status, exercise habit, occupation category, weekly working hour, and working year. After 2 years of intervention, the occupational stress detection rate decreased significantly to 47.82% (P < 0.001), while the high social support rate (19.68%) showed no significant change. Subgroup analysis indicated significant reductions in occupational stress detection rates (all P < 0.05) among individuals aged ≥ 27 years, males, Han Chinese, those with high school or vocational school or higher, married individuals, never or occasional drinkers, firefighters or bus drivers, those working 40–48 or >56 h per week, and those with >6 years of work.ConclusionsOccupational stress is a prominent issue among firefighters, bus drivers, VDT operators, and port workers in Shenzhen, China. Mental health interventions could effectively reduce occupational stress, demonstrating significant value in improving the psychological wellbeing of high-risk populations.